ANALISIS TINGKAT KEANDALAN PENYORTIR (STUDI KASUS DI KANTOR POS MPC SEMARANG 50400) - Arief Budhiman; Purnawan Adi Wicaksono; Rani Rumita (Industrial Engineering Online Journal, 2012)
PT.POS INDONESIA is a company engaged in the services sector in the form of inter-send letters or goods in accordance with the specified time. In sorting mail or goods, there are examples of operator errors such as the wrong sort mail or goods. Operators sometimes enter the wrong letter or items that should be included to the table that reads a region corresponding to the destination address is written, so it can slow down a letter or goods to reach the recipient. This study begins to analyze the factors that affect the reliability of the sorter. Based on the interviews, the occurrence of human error in sorting the items affected by seven factors: 1. Unreliability of infrastructure2. Operator lack of experience in sorting the items3. Operators feel tired when sorting items4. The discrepancy between the amount of time sorting the items supplied5. Lack of training and learning in sorting items6. The process of information delivery that are less well7. Lack of time to inspect the results of an item that has been sorted From the results of the questionnaire, the factors most influencing factor to 1, 4 and  7. To minimize the occurrence of error humman on sorting the mail and goods, the researchers gave some recommendations 1. Table sorting code should not only include pool, but also must include the names of regions of one such pool code, so as to facilitate the sorting process. Because if you just use the code sortingpool  table, sorters sometimes not the master of the pool code. 2. Computers and sensors should be applied routinely care system from being damaged during use. Because the treatment system of the post office is if the computer and sensor equipment has been damaged, the newly improved suggestions. In this case, system maintenance performed 1 month 1 time.3. Sorting process that requires inspection items have been sorted can be sent in accordance with its purpose. In this case, you should need additional time to inspect the results of a sort. Time to inspect about 30 minutes before the item is sent to the purpose.4. Should be added operators to sort the items, so as to facilitate the sorting process.